Beyond the Firm: Business Families as Entrepreneurs. (July 2018) - Le Breton-Miller, Isabelle; Miller, Danny
Business families, we argue, will be core drivers of economic growth over the next decades, particularly in developing markets. We discuss the resources that provide them with advantages in multibusiness and multimarket entrepreneurial initiatives, the family-based challenges and opportunities that drive or pull them toward such initiatives, the environments in which significant business families thrive, and the resulting socioeconomic consequences.